2001
DOI: 10.1111/1468-0297.00609
|View full text |Cite
|
Sign up to set email alerts
|

Trust and Growth

Abstract: Why does trust vary so substantially across countries? This paper presents a general equilibrium growth model in which heterogeneous agents transact and face a moral hazard problem. Agents may trust those with whom they transact, but they also have the opportunity to invest resources in verifying the truthfulness of claims made by transactors. We characterise the social, economic and institutional environments in which trust will be high, and show that low trust environments reduce the rate of investment. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

49
1,186
8
47

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 2,186 publications
(1,290 citation statements)
references
References 41 publications
(51 reference statements)
49
1,186
8
47
Order By: Relevance
“…Some studies have suggested that the most important aspect of social capital is "trust": to be able to trust that people will do what they say they will, that they will not exploit your good will, and that they will have some sympathy for your perspectives and problems. Trust is important in providing a basis for investment activity (Zak and Knack 2001), national and regional trade , and corporate networks (Yeung 1998). Trust reduces transactions costs, increases the propensity to save and invest, and expands the income of its citizens.…”
Section: Contradictions Of Production-reproduction and Industry-financementioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have suggested that the most important aspect of social capital is "trust": to be able to trust that people will do what they say they will, that they will not exploit your good will, and that they will have some sympathy for your perspectives and problems. Trust is important in providing a basis for investment activity (Zak and Knack 2001), national and regional trade , and corporate networks (Yeung 1998). Trust reduces transactions costs, increases the propensity to save and invest, and expands the income of its citizens.…”
Section: Contradictions Of Production-reproduction and Industry-financementioning
confidence: 99%
“…At the narrower level, in a cross-country survey for 41 nations (including the United States), Zak and Knack (2001) provide evidence that higher levels of trust expand investment and income through reducing moral hazard between principals and agents such as "investors" and brokers, which can be generalized to workers and capitalists, creditors and debtors, clients and consultants, insurers and insured, as well as retailers and customers. There was some degree of two-way causation between variables, but controlling for this it was found that a decline in trust in the order of 7 percent points resulted in an annual drop in investment of 1 percentage point; and a decline in trust of 15 percentage points resulted in a annual drop in growth of 1 percentage point.…”
Section: Contradictions Of Production-reproduction and Industry-financementioning
confidence: 99%
See 1 more Smart Citation
“…Putnam (2000) claimed that trust within an organization is the degree to which individuals confide in each other, tactfully discuss sensitive issues, and are confident that fellow members will not abuse their trust. Coleman (1988), Fukuyama (1996), and Zak and Knack (2001) claimed that trust between members of an organization indicates strong levels of social 205 capital exist within that organization. Poulsen and Tingaard Svendsen (2005) went so far to say, "Trust is social capital" (p. 3).…”
Section: Revue Des Sciences De L'éducation De Mcgill • Vol 46 N O 2 mentioning
confidence: 99%
“…2 While transactions with strangers may have been full of danger, mistrust, and exploitation for much of human evolutionary history (Diamond, 1997;Bowles, 1998), at least more recently, since the 19th century, as modern market society and per capita income have grown (Clark, 2008), the norm of exchange has moved from more exclusively personal to more anonymous (North, 1990). Market proliferation, in turn, has reinforced learning of the notion that trust in strangers brings benefits, resulting in greater trustworthiness (Henrich et al, 2001(Henrich et al, , 2010Zak and Knack, 2001;Al-Ubaydli et al, 2013). …”
mentioning
confidence: 99%